1972
DOI: 10.1901/jaba.1972.5-263
|View full text |Cite
|
Sign up to set email alerts
|

INTRINSIC REINFORCERS IN A CLASSROOM TOKEN ECONOMY1

Abstract: An inexpensive, easily managed token economy was used in a normal classroom for one academic year, and data were collected for the entire academic performance in spelling, language, handwriting, and math for that year. During a baseline period, assignment completion was variable. The introduction of a token economy with a point exchange every five days increased assignment completion and decreased variability of performance. An application of a token economy that had a point exchange averaging four days was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 13 publications
4
22
0
Order By: Relevance
“…Teacher attention combined with token reinforcement further reduced off-task behavior. This finding is consistent with numerous token reinforcement studies (i.e., Bushell, Wrobell, and Michaelis, 1968;McLaughlin, 1975;McLaughlin and Malaby, 1972, 1975Wolf, Giles, and Hall, 1968).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Teacher attention combined with token reinforcement further reduced off-task behavior. This finding is consistent with numerous token reinforcement studies (i.e., Bushell, Wrobell, and Michaelis, 1968;McLaughlin, 1975;McLaughlin and Malaby, 1972, 1975Wolf, Giles, and Hall, 1968).…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have used behavior modification principles in classrooms (Barrish, Saunders, and Wolf, 1969;Hall, Lund, and Jackson, 1968;Madsen, Becker, and Thomas, 1968;McLaughlin and Malaby, 1972, 1975O'Leary and Becker, 1967;O'Leary and O'Leary, 1976). However, relatively few behavioral researchers (McAllister, Stachowiak, Baer, and Conderman, 1969;McCullough, 1972; McSween, Note 1; Meyer, Strowig, and Hosford, 1970) have conducted studies with junior high-school students.…”
mentioning
confidence: 99%
“…They suggested that modifying an academic response rate may be more efficient than modifying a process behavior because in the former instance 447 1982,151,[447][448][449][450][451][452][453][454] NUMBER 3 (FALL 1982) teachers are not required to monitor constantly students' studying. A similar conclusion was reached by McLaughlin and Malaby (1972) who reported that fifth and sixth graders completed substantially more assignments when they were rewarded for assignment completion than when they were rewarded for quietness and attentiveness. Together, the studies by Kirby and Shields (1972) and McLaughlin and Malaby (1972) suggest that targeting productivity rather than attentiveness is a more effective means of increasing students' academic performance.…”
supporting
confidence: 70%
“…A similar conclusion was reached by McLaughlin and Malaby (1972) who reported that fifth and sixth graders completed substantially more assignments when they were rewarded for assignment completion than when they were rewarded for quietness and attentiveness. Together, the studies by Kirby and Shields (1972) and McLaughlin and Malaby (1972) suggest that targeting productivity rather than attentiveness is a more effective means of increasing students' academic performance. However, in some settings, such as special education classrooms where students exhibit diverse skill levels, modifying productivity across an entire classroom of students may be difficult.…”
supporting
confidence: 70%
“…In a classroom-wide token economy with fourth and fifth grade students, for example, McLaughlin and Malaby (1972) showed that a subtle change in the exchange schedule-moving exchange opportunities from fixed times once per week to variable times once per weekproduced marked improvements in completion of academic assignments. Such effects have also been seen in several laboratory experiments as well (see review by Hackenberg, 2009), and helps make the point that even small changes in the scheduling of tokens and exchanges can have large and lasting effects on token-producing behavior (in the present case, academic and pro-social behavior).…”
mentioning
confidence: 99%